Managing Cultural Differences : Leadership Strategies for a New World of Business - Harris, Philip R. and Moran, Robert T. (Houston Gulf Publishing Company, 1996)
This guide shows how to develop the cross-cultural expertise essential for succeeding in the world of rapid economic, political and cultural changes. These global market shifts make this edition a useful resource.
Include Index
Keywords: Acculturation -- Cross-cultural studies -- International business enterprises--Management